Missed nursing care in an intensive care unit - Ana Paula Moro Bertoni; Glaucia Fagundes; Bruno de Souza Luchtenberg; Vitoria Rosa Amaral; Josemar Batista (Rev Rene, 2025)
Objective: to examine the prevalence of missed nursing care in an intensive care unit, by professional category and work shift. Methods: this cross-sectional study was conducted in the critical care unit of a teaching hospital. The Missed Nursing Care Survey – Brazil was administered to 38 nursing professionals. Data were analyzed using both descriptive and inferential statistics; p ≤ 0.05 was considered statistically significant. Results: the most frequently missed care activity was patient ambulation three times a day or as prescribed. Labor and material resources were the primary reasons for missed care, with no statistically significant differences between professional categories or work shifts. Participation in interdisciplinary team discussions differed between nurses and nursing technicians (p = 0.027). Lower rates of missed care were observed among daytime staff for four care activities (p ≤ 0.05). Conclusion: a high prevalence of missed nursing care was identified, with differences in the types of care omitted between nurses and nursing technicians, as well as across work shifts. Contributions to practice: these findings support the planning of priority actions to be incorporated into the patient safety plan and highlight the need for further research on the impact of work shift length on missed nursing care.